Community Empowerment Strategy through Management of Lerep Tourism Village, West Ungaran District, Semarang Regency - Febrianti, Leni; Edy Mulyono, Sungkowo (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This study aims to describe the empowerment strategy through the management of tourist villages with a research focus on the stages, strategies and constraints of empowerment in the management of tourist villages. This research uses a descriptive qualitative approach. The research respondents were the head of Lerep village and the director of BUMDes, as informants were the managers of Lerep tourism village. Data collection uses interviews, observation and documentation methods. Data validity using source and method triangulation. Data analysis through the stages of data collection, data reduction, data presentation and conclusion drawing. The results showed that the stages of empowerment carried out in the Lerep tourism village include the awareness stage, the knowledge transformation stage and intellectual improvement. Empowerment strategies in the management of tourist villages are in the form of human resource enhancement, self-management, productive business development, group institutional improvement, and capital development. The obstacles faced in the empowerment of tourism village management are capital problems, constrained awareness process and competitiveness. The conclusion of the research is that the empowerment carried out in the Lerep tourism village has a good impact on the Lerep village community. The management of the tourist village can run well because the villagers have the intellectual power to manage the tourist village. The tourist village has an impact on increasing human resources, improving the economy and developing the village environment.Keywords: Community empowerment, management, tourism village